1987
DOI: 10.1148/radiology.164.3.3303120
|View full text |Cite
|
Sign up to set email alerts
|

Self-expanding endovascular prosthesis: an experimental study.

Abstract: A new type of endovascular prosthesis was inserted in 28 animals and evaluated for several factors, including thrombogenicity, tendency to migrate, critical implant zones, and incorporation into the vascular wall. The new prosthesis is a woven, multifilament structure of stainless steel alloy; its inherent elastic, self-expanding characteristics hold it against the vessel walls. Forty-seven endoprostheses (3-5 mm in diameter, 15-50 mm long) were percutaneously implanted with either a 6-F introducer sheath, a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
7

Year Published

1991
1991
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(52 citation statements)
references
References 0 publications
2
41
1
7
Order By: Relevance
“…The early experimental work on the use of a new self expanding endovascular prosthesis was reported by Rousseau et al [1]. The technique was extended by Mil roy et al [2] who described their experience with the same stent in the normal dog urethra and in the first 8 patients, and by Sarramon et al [3] who reported healing after placing spring stents into the urethra of dogs and The stent is a woven self expanding tubular mesh of fine stainless steel wire (fìg.…”
Section: Introductionmentioning
confidence: 99%
“…The early experimental work on the use of a new self expanding endovascular prosthesis was reported by Rousseau et al [1]. The technique was extended by Mil roy et al [2] who described their experience with the same stent in the normal dog urethra and in the first 8 patients, and by Sarramon et al [3] who reported healing after placing spring stents into the urethra of dogs and The stent is a woven self expanding tubular mesh of fine stainless steel wire (fìg.…”
Section: Introductionmentioning
confidence: 99%
“…5 Intraluminal stents have been used since 1969 to prevent stenosis after balloon angioplasty. 6,7 The use of urethral stents to prevent recurrence of urethral strictures was first reported by Miller et al, 4 and was later tried in a number of European urological units. 8,9 There has been recent enthusiasm about the use of urethral stents in the recurrent urethral strictures, giving good short-term results.…”
Section: Discussionmentioning
confidence: 99%
“…Stents with a higher concentration of metal and with greater degrees of flexibility seem to increase intimal thickness. [20][21][22] Therefore, the widespread strategy of stent implantation only if a suboptimal result is obtained after balloon angioplasty needs to be tested in a randomized trial, although we suggest that there would be a good longterm prognosis for stents aggressively implanted for a suboptimal result after balloon angioplasty.…”
Section: Bail-out Stentingmentioning
confidence: 96%